2009
DOI: 10.1002/da.20538
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band blue-light treatment of seasonal affective disorder in adults and the influence of additional nonseasonal symptoms

Abstract: Narrow bandwidth blue-light therapy proved superior to red-light therapy. Blue-light therapy produced results similar to both previous 10,000 lux visible-spectrum light studies and many medication studies. The use of bright red panels supported claims that wavelengths of approximately 470 nm account for the documented effectiveness of light therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 12 publications
(10 reference statements)
1
51
0
Order By: Relevance
“…The few studies in real-life settings show a clear trend: at least on the subjective level, participants exposed to bright or blue-enriched light tend to feel better and perceive themselves as more alert and less tired. Taken together, the laboratory results, field study evidence, and the fact that blue-enriched light is used as therapeutical tool in treating seasonal affective disorder (44,(45)(46)(47) point to blue-enriched light as a potentially powerful agent.…”
mentioning
confidence: 93%
“…The few studies in real-life settings show a clear trend: at least on the subjective level, participants exposed to bright or blue-enriched light tend to feel better and perceive themselves as more alert and less tired. Taken together, the laboratory results, field study evidence, and the fact that blue-enriched light is used as therapeutical tool in treating seasonal affective disorder (44,(45)(46)(47) point to blue-enriched light as a potentially powerful agent.…”
mentioning
confidence: 93%
“…Previous studies suggest that blue light has the capacity to alter an individual's moods. 22 This suggests that the basal ganglia may share similar reactions to the influence of blue light. The connection between the limbic system and the basal ganglia is known as the neostriatum.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies demonstrated that an intensity of at least 2,000 lux was required to produce positive effects on depression [45], [46]. Remarkably, studies that used low intensity light (176, 400, 1,000 and 1,500 lux) also showed improvements in depression scores [9], [11], [34], [41] suggesting that even low intensity light was effective on mood alleviation. All colours of light (blue, green and white) were effective in improving mood.…”
Section: Light Characteristicsmentioning
confidence: 93%
“…Diagnostic and Statistical Manual of Mental Disorders -III Revision and -IV (DSM-III-R and -IV) were prevalent diagnostic questionnaires in selected articles. Twenty-one studies used Hamilton Depression Rating Scale (HDRS) for scoring mood states [9], [11], [15], [16], [20][21][22][23], [30], [32], [34][35][36][37][38][39][40][41][42][43][44]. The other studies used scales such Geriatric Depression Scale, Major Depression Inventory and The International Classification of Diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation